Novel Heterozygous LMNA Variants Causing Familial Partial Lipodystrophy, Dunnigan Variety - Wadhwa, Akhilesh (J Endocr Soc, 2021)
Familial partial lipodystrophy (FPLD) is a rare, mostly autosomal dominant disorder characterized by selective loss of subcutaneous fat from the extremities. Patients with FPLD are predisposed to insulin resistance, dyslipidemia, diabetes mellitus, cardiac abnormalities (coronary heart disease [CHD], cardiomyopathy and conduction system disorders) and hepatic steatosis. FPLD2 (the Dunnigan variety) is the most common subtype which is caused by heterozygous variants in the lamin A/C (LMNA) gene. Over 50 LMNA causal variants have been reported in patients with FPLD2, with p.R482W and p.R482Q comprising ~75% of the families. We report 5 novel LMNA variants (c.722T>C, p.L241P; c.848A>G, p.N283S; c.1396A>G, p.N466D; c.1543A>G, p.K515E; c.1744C>A, p.R582S) in 5 families, where a female proband presented to us with moderately-severe FPLD, from among a total cohort of 264 FPLD2 families, with 259 families harboring other known pathogenic LMNA variants. The p.L241P variant was found in a 62-year-old female with a body mass index (BMI) of 28 kg/m(2). She had hypertriglyceridemia. She is adopted and has two offsprings, who have not yet been examined and genotyped. The p.N283S variant was found in two males and two females from the same family (Age 40–74 y; BMI 18–45 kg/m(2)). Of these, only the 74-year-old female proband had clinical lipodystrophy, diabetes and hypertriglyceridemia. The other three subjects did not have lipodystrophy. Thus, this variant did not segregate with the phenotype of lipodystrophy in this family likely due to low penetrance or reduced clinical expressivity. The p.N466D variant was found in a 53-year-old female (BMI 26 kg/m(2)) who had diabetes and hypertriglyceridemia. The p.K515E variant was found in 4 females and 1 male who belonged to the same family (Age 29–62 y; BMI 19–26 kg/m(2)). All of them had lipodystrophy and hypertriglyceridemia and three of them had diabetes. The p.R582S variant was found in 3 males and one female who belonged to the same family (Age 19–76 y; BMI 16–30 kg/m(2)). All of them had lipodystrophy but only two of them had diabetes and hypertriglyceridemia. Eight of them had hypertension, three had CHD, one of them had acute pancreatitis and another one had a stroke. None of these patients had cardiomyopathy, cardiac conduction system defects or myopathy. In conclusion, we report genotype-phenotype relationship of 5 novel LMNA variants in patients presenting with FPLD2, with variable prevalence of diabetes, hypertriglyceridemia hypertension and CAD. None of these variants are associated with cardiomyopathy or myopathy or progeroid features. Our report adds to the allelic and clinical heterogeneity associated with LMNA variants.